2011
DOI: 10.1557/opl.2011.237
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Conjugation Enhancement in P3HT/SWNT Mixtures for Organic Photovoltaics

Abstract: Classical molecular dynamics (MD) simulations in conjunction with optical absorption and AFM/nano-Raman experiments are employed to relate the molecular-scale arrangement and conjugation of poly-3-hexylthiophene (P3HT) adsorbed onto single-walled carbon nanotubes (SWNTs) and multi-walled carbon nanotubes (MWNTs). Taken together our results demonstrate the templating role of carbon nanotubes in increasing the π-conjugation length of the P3HT at the P3HT/carbon nanotube interface. The MD simulations show that SW… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Meanwhile, other literature has reported that the thiophene ring modes of P3HT can be identified at 1447 cm -1 (symmetric C = C (stretching), and 1376 cm -1 (C-C intra-ring stretching). These vibrational modes are sensitive to delocalization of πelectron (conjugation length) and peak shift/intensity changes may implied P3HT degree of molecular order [14]. Our analysis on the three spectra shows there is shift in prominent peaks belonged to SWCNT and P3HT.…”
Section: Resultsmentioning
confidence: 70%
See 1 more Smart Citation
“…Meanwhile, other literature has reported that the thiophene ring modes of P3HT can be identified at 1447 cm -1 (symmetric C = C (stretching), and 1376 cm -1 (C-C intra-ring stretching). These vibrational modes are sensitive to delocalization of πelectron (conjugation length) and peak shift/intensity changes may implied P3HT degree of molecular order [14]. Our analysis on the three spectra shows there is shift in prominent peaks belonged to SWCNT and P3HT.…”
Section: Resultsmentioning
confidence: 70%
“…1(a) shows the absorption spectra of pristine P3HT and P3HT/SWCNT films. In both films, two distinct absorption peaks at 562 nm and 615 nm originated from π-π* absorption band of P3HT [13,14]. It is seen that the absorbance intensity of 562 nm peak is higher compared to the 615 nm peak after SWCNT is incorporated into the P3HT film.…”
Section: Resultsmentioning
confidence: 91%